2005
DOI: 10.1287/isre.1050.0064
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of E-Commerce on Competition in the Retail Brokerage Industry

Abstract: This paper analyzes the impact of e-commerce on markets where established firms face competition from Internet-based entrants with focused offerings. In particular, we study the retail brokerage sector where the growth of online brokerages and the availability of alternate sources of information and research services have challenged the dominance of traditional brokerages. We develop a stylized game-theoretic model to analyze the impact of competition between an incumbent fullservice brokerage firm with a bund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 18 publications
1
56
0
3
Order By: Relevance
“…Research has identified new organisational and market forms, and new opportunities and risks (Timmers 1999;Turban, Lee et al 1999;Berryman, Harrington et al 2000), as well as suggesting industries in which e-commerce may have a large impact, eg. financial markets (Bakos et al 2000), tourism and leisure (Chircu and Kauffman, 2000;McCubbrey, 1999), or car dealerships (Watson and McKeown, 1999;Marshall, Sor et al 2000). Notably, these are mainly the services industries involving a concentration of information processing activities, which may be automated, decentralised, open to other potential improvements, or are subject to competition from Internet-only companies, the so called 'cybermediaries' (Jin and Robey 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has identified new organisational and market forms, and new opportunities and risks (Timmers 1999;Turban, Lee et al 1999;Berryman, Harrington et al 2000), as well as suggesting industries in which e-commerce may have a large impact, eg. financial markets (Bakos et al 2000), tourism and leisure (Chircu and Kauffman, 2000;McCubbrey, 1999), or car dealerships (Watson and McKeown, 1999;Marshall, Sor et al 2000). Notably, these are mainly the services industries involving a concentration of information processing activities, which may be automated, decentralised, open to other potential improvements, or are subject to competition from Internet-only companies, the so called 'cybermediaries' (Jin and Robey 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study of financial brokerages, Bakos et al (2005) find that investors using online brokerages can be burdened with hidden costs stemming from lower execution quality, compared to traditional brokerages. In a study comparing stamp auctions in online and offline settings, Dewan and Hsu (2004) find that the lack of information regarding quality in online auctions leads to adverse selection and lower prices compared to traditional auctions.…”
Section: Quality Uncertainty and Online Marketsmentioning
confidence: 99%
“…The degree of informational and oper ational effi ciency determines the extent to which markets are allocationally effective. Information systems can serve as intermediaries between the buyer s and the sellers in a market, creating an "electronic marketplace" that makes it less expensive for buyer s to acquire information about sellers' product offerings and prices [ 5,6]. Thus, one would expect electronic trading systems to re p lace the inefficiencies of traditional face-to-face and telephone systems among buyer s and sellers in the financial market place.…”
Section: Introductionmentioning
confidence: 99%